Theoretical Developments and Practical Innovations in Financial Accounting: A Review of Current Status, Challenges, and Future Trends - Chen, Jinyi (International Journal of Global Economics and Management, 2025)
With the advent of globalization and the digital age, financial accounting, as a core component of corporate management, is undergoing profound changes. This paper provides a comprehensive review of the existing literature on the core theories, modern developments, and technological innovations in financial accounting, focusing particularly on the adoption of International Financial Reporting Standards (IFRS), digital transformation, and the integration of corporate social responsibility (CSR) into financial reporting. By examining technological advances and regulatory changes, the paper further analyzes the main challenges and development trends facing financial accounting in the future. Finally, the paper suggests that financial accounting practices should place greater emphasis on the application of digital technologies and the harmonization of global accounting standards to adapt to a complex economic environment.